Modern approaches in asthma management: Revolutionizing severe asthma treatment with biologics - Zia, Shamail; Farozaan Shamail; Fazail Zia; Vardah Zia; Shamsa Naeem (Journal of the Pakistan Medical Association, 2026)
There have been advancements in the management of asthma among adults over the last two decades. The type 2 processes of airways inflammation and the use of type 2 biomarkers fractional expired nitric oxide and eosinophils have been further illuminated owing to such advancements. Moreover, epithelial cells are appearing as noteworthy elements for inflammation via the production of alarmins to start the local injury along with downstream pathways. Five new biologics have revolutionised severe asthma therapy apart from omalizumab, which are mepolizumab, benralizumab, reslizumab, dupilumab and tezepelumab. These biologics prevent the exacerbations significantly, thereby sparing the use of systemic corticosteroids and their adverse effects. For both rescue and maintenance therapies, the available guidelines prove the efficacy of inhaled corticosteroids and long-acting beta-2 agonists, like formoterol. Future guidelines ought to incorporate phenotype/endotype-focused management to acquire further precision-directed therapy. Key Words: Asthma management, Phenotype/endotype, T2 inflammation and biologics, Adult asthma treatment.